Synchrony does not explain extrapair paternity rate variation in northern or southern house wrens - LaBarbera, Katie (2010)
Rates of extrapair paternity (EPP) vary widely among and within bird species, and 2 hypotheses suggest that this variation is driven by variation in breeding synchrony. These hypotheses make contradictory predictions, and each has some support from field studies, but the general relationship between EPP and synchrony remains unclear. We investigated EPP in relation to population-wide and local breeding synchrony in 2 populations of house wrens (Troglodytes aedon)-a migratory northern temperate (New York, USA) and a sedentary southern temperate (Buenos Aires, Argentina) population-that differ in numerous life-history traits. The northern population had significantly higher EPP rates and modestly but significantly higher local breeding synchrony. Population-wide breeding synchrony did not differ between populations. The proportion of extrapair young within a nest was not related to the nest's population-wide or local synchrony index in either population. These results suggest that across divergent life histories in this species, breeding synchrony does not account for within-population variation in EPP.